Tandem mass tag-based proteomics analysis of type 2 diabetes mellitus with non-alcoholic fatty liver disease in mice treated with acupuncture. Issue 1 (28th January 2022) - Wang, Guan; Li, Mengyuan; Yu, Shuo; Guan, Mengqi; Ma, Shiqi; Zhong, Zhen; Guo, Yihui; Leng, Xiangyang; Huang, Haipeng
Abstract: Objective: To explore the proteomics profiles of hepatocytes of mice treated with acupuncture for type 2 diabetes mellitus (T2DM) with non-alcoholic fatty liver disease (NAFLD). Methods: We used a Tandem mass tag (TMT)-based quantitative proteomics approach to identify proteins with potential molecular mechanisms associated with acupuncture interventions for T2DM with NAFLD. Results : Acupuncture effectively improved body weight, blood glucose, and insulin levels in T2DM with NAFLD mouse models and reversed steatosis within hepatocytes. Quantitative TMT-based proteomics analysis identified a total of 4710 quantifiable proteins and 1226 differentially expressed proteins (DEPs) in the model control group (MCG) compared with the normal control group (NCG). The Acupuncture Treatment Group (ATG) presented in 122 DEPs was compared with the MCG group. We performed a bioinformatics analysis, which revealed that DEPs enriched in the KEGG pathway after acupuncture treatment were mainly involved in the PPAR signaling pathway, fatty acid biosynthesis, fatty acid metabolism, fatty acid elongation, fat digestion and absorption. We used parallel reaction monitoring (PRM) technology to explore the association of aldehyde oxidase 1 (Aox1), acyl-coenzyme A thioesterase 2 (Acot2), perilipin-2 (Plin2), acetyl-CoA carboxylase 1 (Acc), NADP-dependent malic enzyme (Me1), fatty acid synthase (Fasn), ATP-citrate synthase (Acly), fatty acid-binding protein, intestinal (Fabp2) with lipid synthesis, fatty acid oxidation, and hepatocyte steatosis. Conclusions: Our results show that acupuncture can regulate the protein expression of T2DM in the NAFLD mice model, and can effectively improve hepatocyte steatosis, and has potential benefits for the clinical treatment of this disease.